Pendekatan Berbasis Big Data untuk Memetakan Tren Kerajinan Lokal - Ponco, Sapta Hastho; Susanti, Susanti; Mufiedah, Maziyyatul (Politeknik Statistika STIS, 2025)
The utilization of big data derived from online search activity is increasingly recognized as an alternative approach for identifying trends and economic opportunities, particularly within the creative economy sector. This study aims to explore the potential of Indonesia’s local craft subsector by analyzing online search data. Utilizing Google Trends and Natural Language Processing (NLP) techniques, this research maps public interest in craft products across spatial and temporal dimensions. Clustering and trend analysis methods are used to identify search patterns that reflect shifts in consumer preferences. The findings indicate that online search data can serve as an early indicator for capturing market dynamics and supporting evidence-based policy formulation. These results demonstrate that big data approaches can complement conventional surveys by providing a more adaptive, contextual, and real-time understanding of the local craft ecosystem.